Evaluation of the extract obtained as leached of coconut (Cocos nucifera) fiber as a bioestimulant in remediation of a soil contaminated with oil - Marín Velásquez, Tomás Darío; Gota Díaz, Creisvy Nazaret; Ortiz Pinto, Thania Carolina (Enfoque UTE, 2018)
The use of the extract obtained as a leaching of the coconut fiber (Cocos nucifera) as a biostimulant for the remediation of a savanna soil contaminated with heavy oil was evaluated. Through standardized procedures, the main characteristics of the extract, oil and soil were obtained. The soil was contaminated with 100 mL of heavy oil per kilogram. Four experimental units of 1 kg each were established, leaving the first as a pattern without treatment and 3 treated with extract in proportions of 50, 100 and 150 mL, each with 3 replicates distributed at random. The units were left under controlled laboratory conditions and the percentage of oils and fats and the pH were determined every 7 days by means of the EPA 9071b and ASTM D4972 standards, until complying with the Venezuelan standard Decree 2635. It was concluded by means of a Factorial ANOVA analysis, that both the volume of extract applied and the exposure time exert a statistically significant influence on the percentage of oils and fats and the pH with 95% confidence level. All soil units treated with extract reached the limit value established in Decree 2635 at 28 days.